IDDF2019-ABS-0273 Hepatic resection versus transcatheter arterial chemoembolization in resectable infiltrative hepatocellular carcinoma: a propensity score weighted landmark study. (June 2019) - Wang, Yuanqi; Han, Xiao; Chen, Shuling; Peng, Sui; Peng, Zhenwei; Kuang, Ming; Lai, Jiaming
Abstract : Background: Patients with infiltrative hepatocellular carcinoma (iHCC) have a worse prognosis than those with other types of HCC and limited choices of treatments. The efficacy of hepatic resection in iHCC patients was unclear, especially comparing with other treatments. We aim to compare the efficacy of hepatic resection (HR) and transcatheter arterial chemoembolization (TACE) for patients with resectable iHCC Methods: We retrospectively enrolled patients with resectable iHCC who were treated by HR or TACE from four clinical centers. Their overall survival (OS) time was calculated and compared by Log-Rank test. A propensity score-matched (PSM) analysis was performed to reduce selection bias. Results: From January 2010 to December 2017, 178 patients with resectable iHCC were collected (124 patients received HR and 54 patients received TACE) and entered into 6, 9, 12-month landmark analysis. The median overall survival (OS) time was significantly longer in patients treated by HR than TACE (19 vs 11 months, p =0.0041). Landmark analysis limiting survivors after 6, 9, 12 months also showed the benefit of HR over TACE in multi-variables COX regression (all p<0.01). Patients with tumors located in both liver lobes or portal hypertension tended to receive HR rather than TACE. After propensity score matched, 46 pairs were compared and HR obtained better overall survival than TACE (median OS time: 29 vs 11 months, p=0.001). The multi-variables analysis indicated vascular invasion as an independent predictor for worse OS in 6-month landmark subgroup(HR: 2.231, 95%CI: 1.364–3.649, p=0.001), especially for patients with the major trunk of portal vein involved. Conclusions: HR might be an optimal choice for patients with resectable iHCC due to its better survival benefit than TACE. Patients with trombosis in the major trunk of portal vein need multiple department team discussion to decide which therapy to be performed.